Domestic Competition Spurs Exports : The Indian Example - Poddar, Tushar (IMF Working Papers; Working Paper ;, 2004)
India's exports nearly tripled in the 1990s. Decomposing export growth shows that it has been driven by incumbent firms rather than the entry of new firms. By using a new panel on Indian firms and estimating a dynamic discrete-choice model of the firm's decision to export, we find evidence that economic liberalization has led to greater domestic competition, spurring firm efficiency and increasing Indian firms' competitiveness and ability to export. We show that export growth has been an outcome of local firm innovation which has come about due to increased competitive pressure from FDI entry.